1994
DOI: 10.1063/1.467837
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions among the rotator phases of the normal alkanes

Abstract: We present the first calorimetric study of the normal alkanes CH3–(CH2)n−2–CH3 (21≤n≤30) covering the temperature range of the five rotator phases (whose structures were previously identified using x-ray scattering) with sufficient resolution to observe the various rotator to rotator transitions. We find first-order hexagonal–orthorhombic distortion transitions; second-order azimuthal tilt-angle rotation transitions, and two types of second-order tilting transitions, one of which has the higher symmetry phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
238
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(267 citation statements)
references
References 49 publications
25
238
3
Order By: Relevance
“…In terms of DSC analysis, it is the integral of the heat flux above the transition's baseline. We have compared Dh values from our experiments with those available in the literature for RT42 [47] and C23 [34,44] and obtained always good agreement with these values, both for ASC and DSC.…”
Section: Stored Heatsupporting
confidence: 48%
See 3 more Smart Citations
“…In terms of DSC analysis, it is the integral of the heat flux above the transition's baseline. We have compared Dh values from our experiments with those available in the literature for RT42 [47] and C23 [34,44] and obtained always good agreement with these values, both for ASC and DSC.…”
Section: Stored Heatsupporting
confidence: 48%
“…The effect is a bit larger here. Earlier ASC measurements on a series of alkanes showed that the Liq-Rot transition hardly supercools, the authors gave an upper limit of 0.03 K [44]. Our value here is a bit higher, but this may be a consequence of samples of different size, geometry and purity used here, as well as a difference in measuring speed.…”
Section: C23contrasting
confidence: 44%
See 2 more Smart Citations
“…This further complicates any attempts at theoretical modelling of such solid-solid phase transitions. 33,34 Molecular dynamics facilitates investigations and prediction of thermo-physical attributes through displacement of particles, change in energies and radial distribution function. The present study aims to predict mass, thermal and transport properties to compare and analyze the phase change behaviours of various systems under consideration.…”
Section: Introductionmentioning
confidence: 99%